Exploring the Pathophysiological Mechanisms of Acute Gastrointestinal Injury in Acute Exacerbations of Chronic Obstructive Pulmonary Disease: An Integrative Review - Luo, Mingsheng; Wan, Dong (Journal of Contemporary Medical Practice, 2025)
Acute gastrointestinal injury (AGI) complicating acute exacerbations of chronic obstructive pulmonary disease (AECOPD) represents a complex multisystem pathophysiological phenomenon involving systemic inflammation, hypoxemia, microcirculatory dysfunction, and gut microbiota dysbiosis. Inflammatory mediators, such as tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL- 6), along with hypoxia-inducible factor-1 alpha (HIF-1α), serve as key drivers of gastrointestinal dysfunction. Furthermore, microcirculatory disturbances and dysregulated gut-lung axis interactions exacerbate gastrointestinal barrier impairment. This review systematically analyzes the pathophysiological mechanisms of AECOPD complicated by AGI, focusing on inflammation, hypoxia, microcirculatory dysfunction, and gut microbiota imbalance, aiming to provide a theoretical foundation and reference for clinical management.